Effect of Blood Group on Heart Transplant Waitlist Mortality in the Ventricular Assist Device Era. Issue 7 (July 2020) - Vaidya, Gaurang Nandkishor; Trivedi, Jaimin; Vijayakrishnan, Rajakrishnan; Fraser, Gary E.; Slaughter, Mark S.; Birks, Emma; Abramov, Dmitry
Abstract : The effect of blood group on heart transplant list mortality in the era of continuous flow left ventricular assist devices (VADs) is unknown. We sought to examine mortality from the United Network for Organ Sharing (UNOS) database, with focus on mortality among VAD versus non-VAD recipients according to blood group. The UNOS database from 2007 to 2015 was evaluated to compare the rates of waitlist mortality or delisting for clinical worsening at 1-year postlisting among various blood types based on the presence or absence of durable continuous VAD. Patients with pulsatile VAD, temporary VAD, or with incomplete data were excluded. A total of 16, 803 patients met the inclusion criteria. Of these, 2, 663 had a HeartMate II or HeartWare VAD implanted before listing or by 365th day of listing. The rate of adverse events on the waitlist, irrespective of VAD, was highest among group O patients (odds ratio [OR] 1.54, p < 0.001). The use of VAD was associated with significant relative risk reduction (OR 0.43, p < 0.001) in waitlist adverse events among all patients, with relative risk reduction that overall did not vary by blood group. Among VAD recipients, waitlist adverse events were similar across all blood types. Among listed patients, there is a significantly higher adverse event rate in group O patients compared with others, irrespective of VAD use. With implantation of continuous flow HeartMate II or HeartWare VAD, all blood groups experience similar relative benefit and similar rates of adverse events. All patients, but particularly those with blood group O, eligible for VAD as a bridge to transplant should be considered for VAD placement.